Audit Committee, control of Majority Shareholder and Their Impact on Audit Committee Effectiveness: Indonesia Evidence - Sidharta Utama; F. Leonardo Z F. Leonardo Z (The Indonesian Journal of Accounting Research, 2013)
The purpose of this study is to provide empirical evidence about the impact of audit committee composition and the control of firm governance on audit committee effectiveness (ACE), based on a survey of audit committees of publicly listed companies in the Jakarta Stock Exchange. Examining the impact of the control of firm governance by majority shareholders is interesting since the ownership structure of listed companies in Indonesia is still dominated by family ownershipThe study finds that audit committee composition has a positive impact on ACE. But, ACE is also influenced by the control of firm governance by majority shareholders. Our findings are consistent with the hypothesis that majority shareholders perceive audit committees as a threat to their control of the companies, and therefore use their power in the board of commissioners as well as directors to restrict audit committee authority, resources, and efforts.